Validity and Responsiveness of Preference-Based Quality-of-Life Measures in Informal Carers: A Comparison of 5 Measures Across 4 Conditions - McLoughlin, Carol (Value Health, 2020)
OBJECTIVES: Carer quality-of-life (QoL) effects are recommended for inclusion in economic evaluations, but little is known about the relative performance of different types of QoL measures with carers. This study evaluated the validity and responsiveness of 3 care-related QoL measures (the Carer Experience Scale [CES], CarerQoL-7D, and ASCOT-Carer), 1 health-related QoL measure (the EQ-5D-5L), and 1 generic QoL measure (the ICECAP-A). METHODS: Validity and responsiveness were assessed in a UK sample of informal carers of adults with dementia, stroke, mental illness, or rheumatoid arthritis. A questionnaire containing the 5 QoL measures was posted to carers identified through the Family Resources Survey (N = 1004). Hypotheses regarding the anticipated associations between constructs related to the QoL of carers were tested to investigate construct validity and responsiveness. RESULTS: Each measure exhibited some level of construct validity. In general, larger effect sizes and stronger associations were detected for the ASCOT-Carer and ICECAP-A measures in the pooled sample and across all conditions. The 5 measures did not exhibit clear responsiveness to changes over a 12-month period in care recipient health status or hours of care provided per week. CONCLUSION: The results of this study provide initial evidence of the validity of care-related, health-related, and generic QoL (capability) measures in informal carers of adults with 4 highly prevalent conditions. Care-related measures were not always more sensitive to constructs associated with QoL of carers compared with generic measures. The performance of the ICECAP-A was comparable with that of the best-performing care-related measure, the ASCOT-Carer.